P‐Type Charge Transfer Doping of Graphene Oxide with (NiCo)1−yFeyOx for Air‐Stable, All‐Inorganic CsPbIBr2 Perovskite Solar Cells. (25th March 2021) - Du, Jian; Duan, Jialong; Yang, Xiya; Duan, Yanyan; Zhou, Quanzhu; Tang, Qunwei
Abstract: The precise regulation of interfacial charge distribution highly determines the power conversion efficiency of perovskite solar cells (PSCs). Herein, inorganic (NiCo)1− y Fe y O x nanoparticle decorated graphene oxide (GO) is successfully demonstrated as a hole booster for all‐inorganic CsPbIBr2 PSC free of precious metal electrode. Arising from the spontaneous electron transfer induced p ‐type doping of GO from edged oxygen‐containing functional groups to (NiCo)1− y Fe y O x, the best all‐inorganic CsPbIBr2 PSC achieves an efficiency of 10.95 % under one standard sun owing to the eliminated paradox between charge extraction and charge localization in GO surface. Furthermore, the champion device exhibits an excellent long‐term stability at 10 % relative humidity without encapsulation over 70 days because of the suppressed ions migration. Abstract : (NiCo)1− y Fe y O x decorated GO is used as a hole booster in all‐inorganic CsPbIBr2 PSC. A champion efficiency of 10.95 % is achieved arising from the charge transfer doping effect between (NiCo)1− y Fe y O x and GO.